THE PERCEPTION OF PARENT'S ABOUT ONLINE LEARNING USING PROCESS EVALUATION MODEL IN TEJAKULA DISTRICT - Kadek Katarina Dewi Kurniawati (Universitas Islam Lamongan, 2022)
Online learning has been implemented as an alternative to face-to-face learning. The learning process was carried out from home online. Learning at home causes parents to be involved in the learning process of their children. Parents' perspective is needed in knowing the implementation of online learning. This study uses descriptive qualitative research methods. The data was generated using interview instruments and questionnaires with a focus on the process evaluation model. The purpose of this article is to find out the perspective of parents on the online learning process during a pandemic situation. The sample taken is 20 parents of students who are implementing the online learning process in Tejakula sub-district. The results showed that parents were able to provide motivation to students during the learning process. However, there are some obstacles that they cannot control when contributing to learning. Keywords: Online learning, parents perception, process evaluation model